Gouvernorat Kafr esch-Scheich, Ägypten. Landschaftsarchäologie und regionale Siedlungsnetzwerke um den Fundplatz Tell el-Faraʿin (Buto) im Nildelta. Die Arbeiten des Jahres 2018 - Schiestl, Robert (e-Forschungsberichte des DAI, 2018)
The reconstruction of the ancient waterscape in the northwestern Nile delta forms an integral part of the research question of the settlement history of this region. The fundamental changes in the modern landscape proved to be challenging when attempting to trace ancient branches of the Nile by auger coring. The initial hypothesis for the course of a former Nile branch was based on a linear settlement distribution. The recent analysis of a Digital Elevation Model of the region, based on TandemX satellite data, provides a remarkably clear and entirely different picture: a ramified sub delta of smaller branches emerges. The ancient settlements were all founded on levees of these smaller branches.